Comparison of the Suggested loss Function with Generalized Loss Function for One Parameter Inverse Rayleigh Distribution - Emad Farhood AL-Shareefi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The experiences in the life are considered important for many fields, such as industry, medical and others. In literature, researchers are focused on flexible lifetime distribution.